Surface modification of starch based biomaterials by oxygen plasma or UV-irradiation - Pashkuleva, I. (2010)
Radiation is widely used in biomaterials science for surface modification and sterilization. Herein, we describe the use of plasma and UV-irradiation to improve the biocompatibility of different starch-based blends in terms of cell adhesion and proliferation. Physical and chemical changes, introduced by the used methods, were evaluated by complementary techniques for surface analysis such as scanning electron microscopy, atomic force microscopy, contact angle analysis and X-ray photoelectron spectroscopy. The effect of the changed surface properties on the adhesion of osteoblast-like cells was studied by a direct contact assay. Generally, both treatments resulted in higher number of cells adhered to the modified surfaces. The importance of the improved biocompatibility resulting from the irradiation methods is further supported by the knowledge that both UV and plasma treatments can be used as cost-effective methods for sterilization of biomedical materials and devices.